The Book of Inheritance By Sheikh Muhammad bin Abd al-Rashid al-Kirmani  (d. 543 AH) It is part of his book Jewels of Fatwas study and investigation (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the one who was sent as a mercy to the worlds, our master Muhammad Al-Amin, and his family and companions, and those who follow them in goodness until the Day of Judgment.To proceed: The study of Islamic jurisprudence from any aspect brings many benefits to the society in which we live, and to the entire world, and among these benefits: understanding the religion is one of the best deeds, as indicated by the Qur’anic texts and the honorable Sunnah of the Prophet. ِ ِ َ َ َ َ َ ْ َ َ َ ْ َ َ َ َ َ ََ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ ْ َ َ َ َْ َ َْ َْ َْ َْ َْ َْ َْ َْ َْ َْ ََْ ََْ ََْ َ َ َ َ َ َ َ َ َ َ َ َ َ َ َ ْ َ َ َ َ َ َ َ َ ْ َ َ ْ َ َ َ ْ َ َ ْ َ ِ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ To َ َ َ َ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ َ ْ َ To